PENERAPAN METODE GRAMMAR TRANSLATION UNTUK MENGEMBANGKAN KEMAMPUAN TATA BAHASA INGGRIS SISWA SMK SARASWATI - Retno Tri Vulandari, Saly Kurnia Octaviani, Arumsari & (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2017)
The aim of this research is to improve English grammar skill of private vocational students by using Grammar Translation Method (GTM). The grammar itself focuses on simple present tense and simple past tense. Data of this research uses pre â test and post â test of 35 students majoring accounting in SMK Saraswati. Meanwhile, this research was conducted using proportional stratified random sampling for taking its data sample and independent sample t-test for analyzing its data. According to the research result, the average of pre-test (before any treatment) is lower than the post test. The data analysis shows that the average of pre-test is 52 and post test is 76. In this case, students had improvement in understanding the materials after the application of grammar â translation method in classroom. It means that Grammar â Translation Method can improve studentsâ English grammar skill, especially students having trouble to comprehend grammar material in fully English.